Effects of cumulative doses of vinasse on soil microorganisms in cerrado - Tauk, S. M. (My University, 1990)
Counts of colony forming units of actinomycetes, bacteria and filamentous fungi were determined in cerrado soil treated with vinasse (processed sugar cane effluent) for 5 yr, using doses of 20 l m-2a-1 and 50 l m-2a-1. A temporary increase in the counts of actinomycetes and bacteria for some months after the addition of vinasse was observed. An increased number of fungi was detected throughout the experiment together with qualitative changes in the population. The most abundant fungi in cerrado soil not treated with vinasse (control soil) were Chaetomium, yeasts, Mucor, Penicillium and Trichoderma, while in vinasse treated soils, the same genera adding Verticillium, with the exception of yeasts, were the most common fungi. -Author
Keywords: cerrado; soil microorganism; sugar cane effluent; vinasse; Actinobacteria; Actinobacteria (class); Arundinaria; Bacteria (microorganisms); Chaetomium; Fungi; Mucor; Penicillium; Saccharum hybrid cultivar; Trichoderma